Artemis Fowl: The Eternity Code - Colfer, Eoin.; Parker, Nathaniel (New York, N.Y. : Listening Library, 2004)
After Artemis uses stolen fairy technology to create a powerful microcomputer and it is snatched by a dangerous American businessman, Artemis, Juliet, Mulch, and the fairies join forces to try to retrieve it.
aUnabridged.
aCompact discs.
Read by Nathaniel Parker.
Keywords: Children's audiobooks; Adventure and adventurers -- Fiction; Fairies -- Fiction; Magic -- Fiction; Computers -- Fiction; Audiobooks; England -- Fiction